Implementation of Problem-Based Learning with a Deep Learning Approach to Improve Elementary Students’ Critical Thinking Skills - Rizka Munira; Sarah Fazila; Dwhy Dinda Sari (Civiliza Publishing, Indonesia., 2026)
This study is situated within the context of the increasing need to develop students’ critical thinking skills as part of 21st-century competencies, particularly in elementary education where meaningful and active learning is essential. The purpose of this study is to examine the effectiveness of implementing Problem-Based Learning (PBL) integrated with a Deep Learning approach in improving students’ critical thinking skills in IPAS (Integrated Natural and Social Sciences) learning. This study employed a quantitative approach using Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were fourth-grade students of SDN 1 Blang Mangat. Data were collected through observation and written tests based on critical thinking indicators, including interpretation, analysis, evaluation, inference, explanation, and self-regulation, and analyzed using descriptive quantitative techniques. The results showed a significant improvement in students’ critical thinking skills, as indicated by the increase in learning mastery from 60% in Cycle I to 85% in Cycle II. In addition, students demonstrated higher engagement, active participation in discussions, and improved ability to analyze and solve contextual problems. These findings suggest that the integration of PBL with a Deep Learning approach not only enhances students’ critical thinking skills but also promotes meaningful and student-centered learning. Therefore, this approach can be considered an effective instructional strategy for improving the quality of learning in elementary schools, particularly in fostering higher-order thinking skills.